Wealth Differentials in Prevalence of Self- Reported Diabetes Mellitus in Bangladeshi Adults (Cardiovascular Journal, 2020)
Background: We report relationship of wealth indices with self-reported diabetes data in Bangladeshi people. As a secondary objective we examine whether educational achievement can be used as a proxy of wealth indices.Methods: We have analyzed data of a nationally representative STEPS survey (STEPwise Surveillance of NCD risk factors) done in 2010 in 8808 adults selected at their households using a multistage cluster sampling approach to describe association of socioeconomic status with diabetes mellitus. We created wealth indices using principal component analysis based on a 20-item household asset items; and then divided subjects in to quartiles.Results: Prevalence of documented diabetes was 3.9% but it was more than 11 times (9.3%) in the fourth quartile (richest) compared to the first quartile (0.8%). This may either mean that the detection rate is higher among the higher socioeconomic group or there are some intervening factors accompanied by the economic achievements that favors occurrence or detection of diabetes in Bangladeshi adults.Conclusion: Future studies need to identify the factor(s) that provides such a putative effect. Educational achievement also has shown similar trend. Therefore, education might be a proxy variable to determine socioeconomic status instead of a long list of household asset items.Cardiovasc. j. 2020; 13(1): 52-55